THE ROLE OF FARMER GROUPS IN IMPROVING FARMERS’ INDEPENDENCE IN THE MODERN ERA (CASE STUDY IN CISARUA VILLAGE, NAGRAK DISTRICT, SUKABUMI REGENCY) - Reshy Destira Rahmalia; Reny Sukmawani; Ema Hilma Meilani (Universitas Galuh, 2026)
The agricultural sector in the modern era is characterized by the increasing adoption of digital technology, which drives the transformation of agricultural systems. However, farmers still encounter various limitations, particularly in terms of low digital literacy and weak institutional capacity. This study aims to analyze the role of farmer groups in enhancing farmers’ independence and to assess its relevance in addressing agricultural digitalization in Cisarua Village, Nagrak District, Sukabumi Regency.This research applied a quantitative approach using a survey method. Data were collected through questionnaires, interviews, and field observations. The respondents consisted of 30 active members of the Sri Rahayu II Farmer Group. Data analysis was conducted using multiple linear regression with SPSS software.The results indicate that leadership, member participation, and communication have a positive and significant effect on the role of farmer groups, both partially and simultaneously. Leadership is the most dominant variable influencing the role of farmer groups. The coefficient of determination (R²) of 0.586 shows that 58.6% of the variation in the role of farmer groups is explained by the studied variables, while the remainder is influenced by other factors outside the model. Overall, farmer groups have contributed to improving farmers’ independence; however, limitations still exist in communication and digital literacy, which need to be strengthened through technology-based institutional development.farmer groups; farmers’ independence; communication; leadership; agricultural digitalization